Protection and production 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Microlivestock: little-known small animals with a promising economic future 1991 449pp ISBN 0 309 04437 5 pbk BOSTID, 2101 Constitution Avenue NW JH-210 Washington DC, USA